An automatic test platform to verify the security functions for secure WIA-PA wireless sensor networks - Min Wei; Keecheon Kim (International Journal of Distributed Sensor Networks)
Wireless sensor networks are already employed in numerous applications including military, industry, and health. Among the several inherent limitations in wireless sensor network, security is a critical concern. The declared security functions of wireless devices should be well verified. In this study, a security testing method based on security levels is proposed for wireless sensor networks. In addition, an experimental security testing platform for WIA-PA-based wireless sensor networks is implemented. The test results show that the platform is a feasible platform for assessing device security levels in wireless sensor networks.